The Role of Trust in Mediating Influence Quality of Service and Perception of Ease Against the Decision to Pay Taxes - Dian Hamonangan P. Tondang, Defry; Farida Ferine, Kiki; Muharram Ritonga, Husni (International Conference Epicentrum of Economic Global Framework, 2026)
This study aims to analyze the influence of service quality and perception of convenience on the decision to pay taxes with trust as an intervening variable in taxpayers at KPP Pratama Medan Petisah. This study uses a quantitative approach with a survey method. The research population is active individual taxpayers in Sunggal Village, Sei Sikambing B Village, and Tanjung Rejo Village. The research sample totaled 389 respondents who were determined using the Slovin formula with an error rate of 5%. Primary data was collected through the distribution of questionnaires on the Likert scale. The data analysis technique uses Partial Least Squares Structural Equation Modeling with the help of SmartPLS. The results of the study show that the quality of service has a positive and significant effect on the decision to pay taxes and trusts. The perception of convenience also has a positive and significant effect on the decision to pay taxes and trusts. In addition, trust has a positive and significant effect on the decision to pay taxes. The results of the indirect test showed that trust was able to mediate the influence of service quality and the perception of convenience on the decision to pay taxes. The R-square value shows that the quality of service and the perception of ease are able to explain trust by 25.6%, while the quality of service, perception of convenience, and trust can explain the decision to pay taxes by 40.5%. These findings confirm that taxpayers’ decisions in paying taxes can be improved through quality services, an easy-to-use tax system, and trust in tax authorities.